Astrocyte–microglial association and matrix composition are common events in the natural history of primary familial brain calcification. (10th October 2019) - Nahar, Khayrun; Lebouvier, Thibaud; Andaloussi Mäe, Maarja; Konzer, Anne; Bergquist, Jonas; Zarb, Yvette; Johansson, Bengt; Betsholtz, Christer; Vanlandewijck, Michael
Abstract: Primary familial brain calcification (PFBC) is an age‐dependent and rare neurodegenerative disorder characterized by microvascular calcium phosphate deposits in the deep brain regions. Known genetic causes of PFBC include loss‐of‐function mutations in genes involved in either of three processes—platelet‐derived growth factor (PDGF) signaling, phosphate homeostasis or protein glycosylation—with unclear molecular links. To provide insight into the pathogenesis of PFBC, we analyzed murine models of PFBC for the first two of these processes in Pdgfb ret/ret and Slc20a2 −/− mice with regard to the structure, molecular composition, development and distribution of perivascular calcified nodules. Analyses by transmission electron microscopy and immunofluorescence revealed that calcified nodules in both of these models have a multilayered ultrastructure and occur in direct contact with reactive astrocytes and microglia. However, whereas nodules in Pdgfb ret/ret mice were large, solitary and smooth surfaced, the nodules in Slc20a2 −/− mice were multi‐lobulated and occurred in clusters. The regional distribution of nodules also differed between the two models. Proteomic analysis and immunofluorescence stainings revealed a common molecular composition of the nodules in the two models, involving proteins implicated in bone homeostasis, but also proteins not previously linked to tissue mineralization. While the brain vasculature of Pdgfb ret/ret mice has been reported to display reduced pericyte coverage and abnormal permeability, we found that Slc20a2 −/− mice have a normal pericyte coverage and no overtly increased permeability. Thus, lack of pericytes and increase in permeability of the blood–brain barrier are likely not the causal triggers for PFBC pathogenesis. Instead, gene expression and spatial correlations suggest that astrocytes are intimately linked to the calcification process in PFBC.